Riding to Paradise: Pop-Islamism and Muslim Biker Movement in Central Java - Muhammad Rosyid; Syamsul Rijal (Al-Jami'ah: Journal of Islamic Studies, 2025)
This article examines the rise of the Muslim biker movement in Indonesia through an ethnographic case study of Bikers Subuhan (BS), a motorcycle-based community that promotes congregational dawn (Subuh) prayers. Over the past eight years, BS has expanded to 108 chapters across Indonesian cities, driven by interpersonal networks, ritualised rides such as the Safar Ride, and intensive social media engagement. Drawing on Dominik Müller’s concept of Pop-Islamism, which theorizes the integration of Islamist ideas into popular culture, the study analyzes how BS blends religious piety with lifestyle appeal to mobilize urban Muslim youth. Based on six months of fieldwork in Solo, Central Java, including participant observation, digital ethnography, and interviews, the article argues that BS operates less as a hobbyist club and more as an Islamist movement leveraging motorcycle culture for ideological outreach. While it maintains a public image of casual community engagement, it internally circulates Islamist discourses, including support for Islamic law and the establishment of an Islamic state. The study contributes to scholarship on Islamic activism by showing how leisure-based practices function as vehicles for religious and ideological mobilization.[Artikel ini mengkaji kemunculan gerakan biker Muslim di Indonesia melalui studi etnografis terhadap Bikers Subuhan (BS), sebuah komunitas pengendara motor yang mempromosikan salat Subuh berjemaah di masjid. Selama delapan tahun terakhir, BS telah berkembang menjadi 108 cabang di berbagai kota di Indonesia, dengan pertumbuhan yang didorong oleh jejaring antarpribadi, kegiatan touring ritual seperti Safar Ride, dan keterlibatan aktif di media sosial. Menggunakan konsep Pop-Islamisme dari Dominik Müller, yang menyoroti integrasi gagasan Islamisme ke dalam budaya popular, studi ini menganalisis bagaimana BS memadukan kesalehan religius dengan gaya hidup untuk menarik dan menggerakkan pemuda Muslim urban. Berdasarkan penelitian lapangan selama enam bulan di Solo, Jawa Tengah, yang mencakup observasi partisipatif, etnografi digital, dan wawancara, artikel ini berargumen bahwa BS lebih berperan sebagai gerakan Islamis daripada sekadar klub hobi, dengan memanfaatkan budaya motor sebagai sarana penyebaran ideologi. Meskipun menampilkan citra publik sebagai komunitas santai dan inklusif, BS secara internal menyebarkan wacana Islamis, termasuk dukungan terhadap hukum Islam dan negara Islam. Studi ini berkontribusi pada kajian aktivisme Islam dengan menunjukkan bagaimana praktik berbasis hiburan dan gaya hidup dapat menjadi wahana mobilisasi keagamaan dan ideologis.]